Mother daughter widow wife : a novel - Wasserman, Robin (Scribner, 2020)
Left with no memory of who she is, Wendy Doe arrives at the Meadowlark Institute of Memory Research, where she falls under the control of a doctor and his ambitious student, while the daughter she left behind tries to make sense of it all.